Funding Decision and Dividend Policy and Its Implications on Firm Value Through Profitability - Sitti Murniati (AIBPM Publisher, 2018)
The purpose of this study is to analysis funding decision and dividend policy and its implications on firm value through profitability in Manufacturing companies listed on the Indonesia Stock Exchange. This research method is explanatory research with data collection carried out through documentation techniques in the form of company financial statements for 5 years, the period of 2012 to 2016 with the type of data pooling research which is a combination of time series data and cross section. Research subjects are Manufacturing companies listed on the Indonesia Stock Exchange. Data analysis techniques in this study used Path Analysis with SPSS Version 21. The results of this study indicate that 1) the direct effect of funding decision on profitability is insignificant while the direct effect of dividend policy on firm value is significant 2) the direct effect of funding decision and dividend policy on firm value is insignificant while the direct effect of profitability on firm value is significant , and 3) indirectly funding decision through profitability have an insignificant influence on firm value and indirectly dividend policy through profitability has a significant influence on firm value. Keywords: Funding Decision, Dividend Policy, Profitability and Firm Value